Chemical Sensors Based on Metal–Organic Frameworks. Issue 8 (2nd June 2016) - Yi, Fei‐Yan; Chen, Dongxiao; Wu, Meng‐Ke; Han, Lei; Jiang, Hai‐Long
Abstract: Metal–organic frameworks (MOFs) as chemical sensors have developed rapidly in recent years. There have been many papers concerning this field and interest is still growing. The reason is that the specific merits of MOFs can be utilized to enhance sensitivity and selectivity by various energy/charge transfers occurring among different ligands, ligand, and metal centers, such as from ligands to metal centers or metal centers to ligands, as well as from MOF skeletons to guest species. This review intends to provide an update on recent progress in various applications of different MOF‐based sensors on the basis of their luminescent and electrochemical responses towards small molecules, gas molecules, ions (cations and anions), pH, humidity, temperature, and biomolecules. MOF‐based sensors function by utilizing different mechanisms, including luminescent responses of "turn‐on" and "turn‐off", as well as electrochemical responses. Abstract : Come to your sensors ! This review provides an update on various metal–organic framework (MOF)‐based chemical sensors and their classification on the basis of different mechanisms of luminescent ("turn‐on" and "turn‐off") and optoelectronic responses (see figure). There are many examples of turn‐off detection, but far fewer of turn‐on detection. MOF‐based electrochemical sensors, in particular, are in their infancy.